Simultaneous detection of Streptococcuspneumoniae and prevention of carryover contamination using multiple cross displacement amplification with Antarctic thermal sensitive uracil-DNA-glycosylase and a lateral flow biosensor. Issue 3 (19th January 2021) - Yan, Linlin; Zhao, Fan; Niu, Lina; Cai, Yu; Wu, Lei; Zhu, Xiaoxue; Nong, Jinqing; Hu, Shoukui
ABSTRACT: Streptococcus pneumoniae is an important clinical pathogenic bacterium that is the primary cause of meningitis, septicemia and community-acquired pneumonia. The mortality rate of pneumococcal disease is high, especially in children younger than 5-years-old. Rapid and accurate detection of S . pneumoniae is critical for clinical diagnosis. A ply gene-based multiple cross displacement amplification (MCDA) assay, amplifying DNA under 65°C for 40 min, was established to detect S . pneumoniae . Antarctic thermal sensitive uracil-DNA-glycosylase (AUDG) was applied to prevent carryover contamination. A lateral flow biosensor (LFB) was used to indicate the MCDA results. The ply -MCDA assay could detect as low as 10 fg of S. pneumoniae DNA and 447 colony forming units (CFU)/mL of spiked sputum samples. The analytical sensitivity of the ply -MCDA assay to detect clinical specimens was 100 times higher than that of PCR. The specificity of the ply -MCDA assay was evaluated using 15 S . pneumoniae strains and 25 non- S. pneumoniae strains, which confirmed the high selectivity of the ply -MCDA assay for S . pneumoniae . The AUDG enzyme could effectively eliminate carryover contamination and thus prevented false-positive results. In conclusion, ply -AUDG-MCDA-LFB is a simple, rapid and accurate method to detect S . pneumoniae . Abstract : Simultaneous Streptococcus pneumoniae detection and elimination of carryover contamination with Antarctic thermal sensitive uracil-DNA-glycosylase-supplemented multiple cross displacement amplification in a lateral flow biosensor.